1991
DOI: 10.1002/etc.5620100313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effects associated with an oil platform, using the sediment quality triad

Abstract: The Sediment Quality Triad concept, which incorporates components of sediment chemistry, toxicity (= bioassay tests) and benthic community structure, was applied to the area immediately surrounding a commercial oil and gas production site in the Gulf of Mexico. The results of this study indicated that stations within a 25‐m radius of a central platform and at a remote platform had high levels of sediment chemical enrichment and high toxicity, as determined in laboratory sediment toxicity tests. Benthic communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…Triad studies are usually descriptive; however, Chapman et al [52] reported procedures for using the Triad to develop numerical criteria. The Triad has been used in several ways: (a) t o identify and differentiate pollution-degraded areas in marine, estuarine, and freshwater sediments; (b) to determine concentrations of contaminants associated with effects; (c) to predict where degradation may occur based on chemistry and toxicity; and (d) to rank areas for possible remediation [52].…”
Section: Sediment Quality Triadmentioning
confidence: 99%
“…Triad studies are usually descriptive; however, Chapman et al [52] reported procedures for using the Triad to develop numerical criteria. The Triad has been used in several ways: (a) t o identify and differentiate pollution-degraded areas in marine, estuarine, and freshwater sediments; (b) to determine concentrations of contaminants associated with effects; (c) to predict where degradation may occur based on chemistry and toxicity; and (d) to rank areas for possible remediation [52].…”
Section: Sediment Quality Triadmentioning
confidence: 99%
“…Chapman et al 1991) (De Pauw and Vanhooren 1983) and is based on the taxonomic diversity of the benthic macroinvertebrate community and the presence or absence of specific Fig. 1 Overview of the distribution of the 360 sediment sampling sites in unnavigable watercourses throughout Flanders, Belgium Aquat Ecol (2007) 41:427-441 429 indicator taxa in the sediment sample.…”
Section: Datasetmentioning
confidence: 99%
“…Similar gradients around drilling platforms occur in other parts of the world (e.g. the Gulf of Mexico; Chapman et al 1991b). The drilling site gradient only showed possible effects at the original source; previous studies (de Jong et al 1991 along this gradient have shown contamination, toxicity and benthos alteration (a Triad indicating pollution-induced degradation) extending in 1988 for 500 to 750 m from the center of drilling.…”
Section: Status Of North Sea Sedimentsmentioning
confidence: 68%